Menelusuri Peluang Pengembangan Kajian Tasawuf di Masa Depan melalui Penelaahan Analisis Bibliometrik - Huda, Ali Anhar Syi'bul; Hamdi, Hamdi; Nurhuda, Abid; Mahbubi, M.; Lathif, Nur Muhammad (CT. Rajawali media Utama, 2025)
Sufism often becomes a myth, not a science because it cannot be scientifically proven even to the level of prohibition. However, underestimated it is Sufism has been a part of Islamic science since its emergence during the time of the Prophet until now. For Sufism not to stagnate, it needs to be developed with various formulas following the times. Based on this background, this research aims to explore opportunities for the development of Sufism studies in the future through bibliometric analysis. The research design uses a qualitative approach with bibliometric research methods. The data source used 1000 articles from the search results of articles from the database on crossref with the help of the publish or perish (PoP) application which was then analyzed descriptively. The results concluded that Sufism research in the last 10 years (2014-2024) experienced fluctuating conditions with the highest peak of publications occurring in 2020 as many as 186 studies. The most sources of publication through e-journals are 783 journals and e-proceedings as many as 5 articles. It is also known that 5 productive researchers in the field of Sufism include Rizal Fauzi, Muhammad Azka Maulana, Abdul Kadir Riyadi, Abdur Rohman, and Sulaiman. As for the results of VosViewer mapping, some topics of Sufism that can be developed and have not been researched by many people in the future are related to values, santri, approaches, qualitative, sharia, culture, interviews, pluralism, al wujud, ibn arabi, Ittihad, gratitude, Aceh and the archipelago.